Penerapan Teknik Seo (Search Engine Optimization) pada Website dalam Strategi Pemasaran melalui Internet - Rony Baskoro Lukito; Cahya Lukito; Deddy Arifin (Bina Nusantara University, 2014)
The purpose of this research is how to optimize a web design that can increase the number of visitors. The number of Internet users in the world continues to grow in line with advances in information technology. Products and services marketing media do not just use the printed and electronic media. Moreover, the cost of using the Internet as a medium of marketing is relatively inexpensive when compared to the use of television as a marketing medium. The penetration of the internet as a marketing medium lasted for 24 hours in different parts of the world. But to make an internet site into a site that is visited by many internet users, the site is not only good from the outside view only. Web sites that serve as a medium for marketing must be built with the correct rules, so that the Web site be optimal marketing media. One of the good rules in building the internet site as a marketing medium is how the content of such web sites indexed well in search engines like google. Search engine optimization in the index will be focused on the search engine Google for 83% of internet users across the world using Google as a search engine. Search engine optimization commonly known as SEO (Search Engine Optimization) is an important rule that the internet site is easier to find a user with the desired keywords.